Activities of the Primary and Supplementary Motor Areas Increase in Preparation and Execution of Voluntary Muscle Relaxation: An Event-Related fMRI Study - Toma, Keiichiro; Honda, Manabu; Hanakawa, Takashi; Okada, Tomohisa; Fukuyama, Hidenao; Ikeda, Akio; Nishizawa, Sadahiko; Konishi, Junji; Shibasaki, Hiroshi (The Journal of neuroscience, 1999)
Brain activity associated with voluntary muscle relaxation was examined by applying event-related functional magnetic resonance imaging (fMRI) technique, which enables us to observe change of fMRI signals associated with a single motor trial. The subject voluntarily relaxed or contracted the right upper limb muscles. Each motor mode had two conditions; one required joint movement, and the other did not. Five axial images covering the primary motor area (M1) and supplementary motor area (SMA) were obtained once every second, using an echoplanar 1.5 tesla MRI scanner. One session consisted of 60 dynamic scans (i.e., 60 sec). The subject performed a single motor trial (i.e., relaxation or contraction) during one session in his own time. Ten sessions were done for each task. During fMRI scanning, electromyogram (EMG) was monitored from the right forearm muscles to identify the motor onset. We calculated the correlation between the obtained fMRI signal and the expected hemodynamic response. The muscle relaxation showed transient signal increase time-locked to the EMG offset in the M1 contralateral to the movement and bilateral SMAs, where activation was observed also in the muscle contraction. Activated volume in both the rostral and caudal parts of SMA was significantly larger for the muscle relaxation than for the muscle contraction ( p < 0.05). The results suggest that voluntary muscle relaxation occurs as a consequence of excitation of corticospinal projection neurons or intracortical inhibitory interneurons, or both, in the M1 and SMA, and both pre-SMA and SMA proper play an important role in motor inhibition.